Controllable Rotations of Spiraling Elliptic Beams in Anisotropic Linear Media - Guo Liang; Tingjian Jia; Zhanmei Ren (IEEE Photonics Journal)
We study the rotation properties of spiraling elliptic beams in the anisotropy media. Based on the Collins formula, we obtain the exact analytical solution of the spiraling elliptic beams carrying the orbital angular momentum (OAM) to the paraxial wave equation. It is found that the rotation property is closely relevant to the OAM, which can be controlled by the linear anisotropy of media. For an anisotropic media such as the uniaxial crystal, the rotation velocity of spiraling elliptic beams at the output can be controlled only by changing the direction of the optic axis of the uniaxial crystal. Depending on the anisotropy parameter, two rotation modes are predicted for the spiraling elliptic beam. For small anisotropy parameter, the rotation direction of the spiraling elliptic beam is inverted at a certain propagation distance. When the anisotropy parameter is large enough, the invertion of the rotation direction disappears. The results are potentially useful in controlling the optical beams.